INVENTARISASI JENIS GASTROPODA EKONOMIS PENTING DI MALUKU BAGI SISWA SISWI SDN 170 MALUKU TENGAH - ASILULU - Supusepa, Junita; Loupatty, Sven R; Rijoly, Fredik; Ratuluhain, Eva Susan; Saleky, Valentine D (Balobe: Jurnal Pengabdian Masyarakat, 2023)
Maluku is one of the archipelagic provinces which is famous for its sea area. The diversity of resources in Maluku needs to be optimally managed. However, there are various pressures on the marine environment due to irresponsible use, it requires human resources who are experts and skilled in managing the potential of these resources. Informal education in the form of counseling and community service will be very beneficial, especially for the younger generation (students). This counseling activity aims to provide students with knowledge about economically important gastropod resources in Maluku. The method used is the delivery of extension materials in order to introduce the marine and coastal environment, the types of gastropods and their benefits. This activity was focused on students in grades 5 and 6. The counseling activity was held on September 15 2022 at SDN 170 Central Maluku - Asilulu school. In general, the students were very interested in this counseling activity. This is evidenced by the interaction of questions and answers with the students. They have been able to understand the importance of maintaining economically important gastropod resources and maintaining their sustainability through practical knowledge about understanding the utilization of available resources.